2013
DOI: 10.1038/bjc.2013.296
|View full text |Cite
|
Sign up to set email alerts
|

Biological evidence for a causal role of HPV16 in a small fraction of laryngeal squamous cell carcinoma

Abstract: Background:Human papillomavirus (HPV) is a causal factor in virtually all cervical and a subset of oropharyngeal squamous cell carcinoma (OP-SCC), whereas its role in laryngeal squamous cell carcinoma (L-SCC) is unclear.Methods:Formalin-fixed paraffin-embedded (N=154) and deep-frozen tissues (N=55) of 102 L-SCC patients were analysed for the presence of 51 mucosal HPV types. HPV DNA-positive (HPV DNA+) cases were analysed for E6*I mRNA transcripts of all high risk (HR)/probably/possibly (p)HR-HPV identified, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
131
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 52 publications
(93 reference statements)
12
131
0
2
Order By: Relevance
“…New data on etiopathogenesis, with a specific focus on the role of human papillomavirus (HPV) infection in precursor lesions, CSCC and subtypes, are discussed in this section [1][2][3][4][5][6]. The recently clarified probable pathogenetic mechanism of spindle cell SCC (SpSCC) is also presented [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…New data on etiopathogenesis, with a specific focus on the role of human papillomavirus (HPV) infection in precursor lesions, CSCC and subtypes, are discussed in this section [1][2][3][4][5][6]. The recently clarified probable pathogenetic mechanism of spindle cell SCC (SpSCC) is also presented [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In an additional study, Halec and co-workers revealed that HPV 16 had a causative role only in a small subset of laryngeal SCC (\5 % of 102 tumors) [39]. Although the authors found at least one HPV DNA positive sample in 35 % of patients, they stressed that the mere detection of HPV DNA is not sufficient to identify HPV-driven cancers, since high-risk HPV has frequently been found in benign laryngeal lesions and in normal mucosa [39,41]. In this study, the authors looked for the presence of 51 HPV types, viral load, HPV mRNA expression and expression of p16, pRb, p53 and cyclinD1 to provide reliable findings of transcriptionally active HPV [39].…”
Section: Important Differences Between Cervical and Head And Neck Silsmentioning
confidence: 97%
“…In contrast to anogenital SCC, the prevalence of HPV in laryngeal SCC varies considerably, from 3 to 60 % [38,39]. Li and co-workers [40] recently published a meta-analysis with 55 studies, addressing HPV prevalence in laryngeal SCC.…”
Section: Important Differences Between Cervical and Head And Neck Silsmentioning
confidence: 99%
See 2 more Smart Citations